Montaigne's English journey : reading the essays in Shakespeare's day - Hamlin, William M., 1957- (Oxford University Press, 2013)
'Montaigne's English Journey' provides a vivid account of the way in which English readers made sense of Montaigne's 'Essays' during the seventeenth century and how it influenced their own writing.